Medication side effects and retention in HIV treatment: a regression discontinuity study of tenofovir implementation in South Africa and Zambia - Brennan, Alana T.; Bärnighausen, Till (American journal of epidemiology, 2018)
Abstract: Tenofovir is less toxic than other nucleoside reverse-transcriptase inhibitors used in antiretroviral therapy (ART) andmay improve retention of human immunodeficiency virus (HIV)–infected patients on ART. We assessed the impact ofnational guideline changes in South Africa (2010) and Zambia (2007) recommending tenofovir forfirst-line ART. Weapplied regression discontinuity in a prospective cohort study of 52,294 HIV-infected adults initiatingfirst-line ART within12 months (±12 months) of each guideline change. We compared outcomes in patients presenting just before and afterthe guideline changes using local linear regression and estimated intention-to-treat effects on initiation of tenofovir,retention in care, and other treatment outcomes at 24 months. We assessed complier causal effects among patientsstarting tenofovir. The new guidelines increased the percentages of patients initiating tenofovir in South Africa (risk dif-ference (RD)=81 percentage points, 95% confidence interval (CI): 73, 89) and Zambia (RD=42 percentage points,95% CI: 38, 45). With the guideline change, the percentage of single-drug substitutions decreased substantially inSouth Africa (RD=−15 percentage points, 95% CI:−18,−12). Starting tenofovir also reduced attrition in Zambia(intent-to-treat RD=−1.8% (95% CI:−3.5,−0.1); complier relative risk=0.74) but not in South Africa (RD=−0.9%(95% CI:−5.9, 4.1); complier relative risk=0.94). These results highlight the importance of reducing side effects forincreasing retention in care, as well as the differences in population impact of policies with heterogeneous treatment ef-fects implemented in different contexts
Gesehen am 15.08.2019